Implementation of Interactive Multimedia Design Principles in a Prototype Website for a Higher Education Research Institution - Irma Delianti, Vera; Giatman, M; Irfan, Dedy; Effendi ​, Hansi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
University research institute websites play a strategic role as media for disseminating research outputs and community service activities to the public. However, many institutional websites remain static, offer minimal interactivity, and insufficiently consider user experience. This study aims to examine the contribution of interactive multimedia design principles to improving the quality of information delivery and user interaction on university research institute websites. The research adopts a research and development approach, encompassing stages of user and content needs analysis, information architecture design, wireframe development, visual design, and interaction and navigation design. The results indicate that the application of visual consistency, clear information hierarchy, meaningful integration of text and visuals, and intuitive navigation can enhance readability, accessibility, and user engagement. The implementation of interactive multimedia design supports a more professional and effective institutional image as a medium of organizational communication. This study is limited to the design and implementation stages without empirical usability evaluation.Keywords — Interactive Multimedia Design, Institutional Website, User Experience, Research Institute, Higher Education